RETRACTED ARTICLE: Serum levels of PTEN mRNA in colorectal cancer: a case-control study - Yang Yan; Xiaohui Du; Shaoyou Xia; Songyan Li; Da Teng; Shidong Hu; Yufeng Wang; Rong Li (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Yang Yan, Xiaohui Du, Shaoyou Xia, Songyan Li, Da Teng, Shidong Hu, Yufeng Wang & Rong Li (2020) Serum levels of PTEN mRNA in colorectal cancer: a case-control study. Artificial Cells, Nanomedicine, and Biotechnology, 48:1, 789–793, DOI: 10.1080/21691401.2019.1576708It has come to our attention that the full authorship list and affiliations for this manuscript were changed after the article was accepted. We have contacted the corresponding author for an explanation, but we have not received a satisfactory explanation. As determining authorship is core to the integrity of published work, we are therefore retracting the article. The corresponding author listed in this publication has been informed.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.